Influence of intergenerational support on the mental health of older people in China. - Zicheng Jiang; Huan Liu; Jing Deng; Yizhong Ye; Dexun Li (PLoS ONE, 2024)
Today, population aging is the main trend of population development. Home-based care is mainly adopted in Chinese society, and scholars have paid ample attention to the effect of intergenerational support on the mental health of older people. However, research conclusions differ. This study uses data from the 2018 China Health and Pension Tracking Survey (CHARLS), which we analyzed with STATA software to construct least squares regression and two-stage least squares regression models. The regression model included 6,647 respondents to investigate the mental health status of older people based on depression status. Intergenerational support was defined as economic support, emotional support, and daily care provided by the children of older people. We studied the impact of three aspects of intergenerational support on the mental health of the elderly. We performed a robustness test using the variable replacement and propensity score matching methods, and analyzed age, gender, and urban-rural heterogeneity. The results showed that economic support had no significant impact on the mental health of older people, while emotional support and daily care had a positive effect. The heterogeneity results indicated that the relationship between intergenerational support and mental health of older people differed significantly based on age, gender, and urban and rural areas. Therefore, children should raise their awareness of supporting their parents, pay attention to their parents' mental health, and provide emotional support and daily care. Furthermore, community work improves family relations, creates a good social environment, and encourages young people to respect and be filial to older people. The government should improve the medical security system and old-age service system, and provide policy support to help the mental health of older people.